2010
DOI: 10.1161/strokeaha.109.569426
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Stenting in Octogenarians

Abstract: on behalf of the CAPTURE 2 Investigators and Executive Committee Background and Purpose-Carotid ACCULINK/ACCUNET Post Approval Trial to Uncover Rare Events (CAPTURE 2) is an ongoing prospective, nonrandomized, multicenter clinical trial enrolling patients undergoing carotid artery stenting.The aim of this analysis is to identify risk predictors for periprocedural stroke in patients Ն80 years old. Methods-Symptomatic patients with Ն50% stenosis and asymptomatic patients with Ն80% stenosis were enrolled.Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…One of the major strengths of this study is that we were able to evaluate and adjust for important clinical and procedural factors, such as high surgical risk status 31 and symptomatic status, 32 which have been associated with poor outcomes after CAS. In using mortality as the outcome, we selected the hardest and most reliable end point.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…One of the major strengths of this study is that we were able to evaluate and adjust for important clinical and procedural factors, such as high surgical risk status 31 and symptomatic status, 32 which have been associated with poor outcomes after CAS. In using mortality as the outcome, we selected the hardest and most reliable end point.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In our study, age was not an important factor in determining the incidence of permanent neurologic deficits during the periprocedural period. Similarly, in other monocentric studies, there is no evidence of a causal link between perioperative neurologic complications and advanced age (Bacharach et al., 2010; Chrysant, Prabhu, Tebow, & Snowden, 2009), although several RCTs showed an increased incidence of complications in octogenarians (Chaturvedi, Matsumura, Gray, Xu, & Verta, 2010; Hobson et al., 2004). …”
Section: Discussionmentioning
confidence: 99%
“…No hypothesis of noninferiority was prespecified for octogenarian patients. Although octogenarians were included in the randomization phase of CREST, published outcome data in CEA were sparse (eg, octogenarians were excluded from landmark randomized CEA studies, including the North American Symptomatic Carotid Endarterectomy Trial and the Asymptomatic Carotid Atherosclerosis Study) and outcomes in CAS patients identified octogenarian status as a predictor of adverse outcomes, 12 which raised concerns regarding the lack of clinical equipoise between CAS and CEA for this patient population in CREST. Therefore, before data unblinding, a prespecified noninferiority analysis for nonoctogenarians was agreed on with the FDA and added to the Statistical and Analytic Plan.…”
Section: Fda Prespecified Analysesmentioning
confidence: 99%
“…Since 2002, the device has had regulatory approval in Europe and has been commercialized in Ͼ85 countries, with no 12,[15][16][17][18] Since conducting ARCHeR, rates of 30-day DSMI with the ACCULINK/ ACCUNET system have been noticeably reduced; specifically, 30-day DSMI rates for ARCHeR, CAPTURE, and CAPTURE 2 were 8.3%, 6.1%, and 3.5%, respectively. These studies, representing Ͼ180 sites and 450 operators in the United States, established the safety and effectiveness of the device for patients at high surgical risk in nontrial clinical settings.…”
Section: Regulatory Perspective On Study Device Preexisting Fda Appromentioning
confidence: 99%
See 1 more Smart Citation